Oribatula (Zygoribatula) nicora - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Oribatula (Zygoribatula) nicora (Djaparidze, 1985) Material – Twelve specimens in Karadedeoğlu Village, Taşköprü forest, N 41° 22′ 55.11′′, E 34° 24′ 03.56′′, alt. = 1204 m, 24 July 2018, tree bark and debris of P. nigra; 21 specimens in Yeşiltepe Area, Akçaabat, Trabzon, N 40° 58′ 24.75′′, E 39° 30′ 25.55′′, alt. = 348 m, 22 May 2018, tree bark and debris of P. abies; one specimen in Alasökü Village, Taşköprü, N 41° 19′ 56.66′′, E 34° 24′ 24.72′′, alt. = 1468 m, 16 June 2018, tree bark and debris of P. sylvestris; three specimens in Çamkonak Forest Processing Area, Daday forest, N 41° 23′ 3.74′′, E 33° 14′ 02.03′′, alt. = 1382 m, 19 October 2018, tree bark and debris of P. nigra. Previous records in Turkey – Halaçli, Taşköprü Kabalar, Merkez Uzunkavak, Taşköprü Kızılcaören, Taşköprü Ağcıkişi, Merkez Çavundur, Hanönü Kornapa, Taşköprü Ağcıkişi villages in Kastamonu region (Murvanidze et al. 2018). Global distribution – Caucasus. Ecology – All types of habitats.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 265, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Oribatula nicora; Arthropoda; Oribatulidae; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Oribatula; Taxonomy; 15. Life on land